Common Terms Between Logicians and Prammarians - Mahmoud, Nashat A. (Humanities Journal of University of Zakho, 2013)
Research in common terms between logicians and prammarians is regarded as important and it is essential for researchers of the Arabic language particularly prammarians> Grammarians included logical terms in their books and defined them logically. This matter causes a problem in misunderstanding the definition when applied in linguistic reality as grammarians view words that convey meaning where as logicians view the whole meaning primarily. Thus, the view of grammarians differs from that of logicians. It is not correct to include a terma in science with its form and definition in another if the term has its characteristics and associations.